Congenital cytomegalovirus infection and small for gestational age infants. (15th April 2014) - Simonazzi, Giuliana; Curti, Alessandra; Murano, Paola; Cervi, Francesca; Contoli, Margherita; Lazzarotto, Tiziana; Capretti, Maria Grazia; Rizzo, Nicola; Guerra, Brunella
Abstract Objective To evaluate the incidence of infants with birth weight less than the 10th centile for small for gestational age (SGA) in primary maternal cytomegalovirus (CMV) infection and to determine whether SGA predicts poor neurodevelopmental outcome. Methods A retrospective cohort study, which included singleton live‐born infants from pregnancies complicated by primary maternal CMV infection. Infants were classified as uninfected or infected based on viral virus isolation and real‐time PCR in urine at birth. SGA neonates rate and long‐term sequelae were evaluated. Results Between 2000 and 2012, 848 women with primary CMV infection were referred to our center with 588 infants assessed at birth. Congenital CMV infection was diagnosed in 119 cases (20%), of which 8 were SGA (6.7%) compared with 27 out of the 469 uninfected infants (5.7%) (p‐value = 0.69). Among the 119 infected babies, 14 infants were symptomatic at birth or at postnatal follow‐up (12%), of whom two were SGA compared with six out of the 105 asymptomatic neonates (5.7% versus 15%, respectively, p‐value = 0.22). Conclusion Congenital CMV infection does not seem to be associated with a higher incidence of SGA, and long‐term outcomes do not seem to be affected by isolated impaired fetal growth. © 2014 John Wiley & Sons, Ltd.